2023
DOI: 10.3390/life13020264
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of Plant-Based Dietary Components in Post-Translational Modifications Associated with Colorectal Cancer

Abstract: Colorectal cancer (CRC) is one of the most common cancers worldwide. Its main modifiable risk factors are diet, alcohol consumption, and smoking. Thus, the right approach through lifestyle changes may lead to its prevention. In fact, some natural dietary components have exhibited chemopreventive activity through modulation of cellular processes involved in CRC development. Although cancer is a multi-factorial process, the study of post-translational modifications (PTMs) of proteins associated with CRC has rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 176 publications
0
3
0
Order By: Relevance
“…Numerous natural products are being considered for research and production of new safe and reliable substances for cancer prevention. The importance of different natural supplements such as polyphenols and flavonoids for cancer prevention has been extensively researched, and there is much circumstantial evidence that a relatively high intake of fruits and plant foods is associated with a reduced risk of CRC ( Lee et al, 2020 ; Wang et al, 2020 ; Ahmad et al, 2022 ; Amintas et al, 2022 ; Mahmod et al, 2022 ; Rodríguez-García and Gutiérrez-Santiago, 2023 ). It has already been reported that these natural compounds are able to influence gene expression and their end products with their versatile modulatory signaling pathways, which allows them to regulate many events in the cell, such as the cell cycle, differentiation, survival, migration, and apoptosis ( Shweiki et al, 1992 ; Dashwood et al, 1999 ; Latruffe et al, 2002 ; Mohamed et al, 2004 ; Shen et al, 2007 ; Pan et al, 2011 ; Costea et al, 2018 ; Pérez-Escalante et al, 2018 ; Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous natural products are being considered for research and production of new safe and reliable substances for cancer prevention. The importance of different natural supplements such as polyphenols and flavonoids for cancer prevention has been extensively researched, and there is much circumstantial evidence that a relatively high intake of fruits and plant foods is associated with a reduced risk of CRC ( Lee et al, 2020 ; Wang et al, 2020 ; Ahmad et al, 2022 ; Amintas et al, 2022 ; Mahmod et al, 2022 ; Rodríguez-García and Gutiérrez-Santiago, 2023 ). It has already been reported that these natural compounds are able to influence gene expression and their end products with their versatile modulatory signaling pathways, which allows them to regulate many events in the cell, such as the cell cycle, differentiation, survival, migration, and apoptosis ( Shweiki et al, 1992 ; Dashwood et al, 1999 ; Latruffe et al, 2002 ; Mohamed et al, 2004 ; Shen et al, 2007 ; Pan et al, 2011 ; Costea et al, 2018 ; Pérez-Escalante et al, 2018 ; Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A CRC prevention strategy may involve the use of dietary supplements providing higher concentrations of specific nutrients with anti-inflammatory and antioxidant properties, modulating the gut microbiota, maintaining intestinal homeostasis, and regulating immune responses [ 10 ]. In that sense, seed oils, especially cold-pressed seed oils, laden with polyunsaturated fatty acids (PUFA), sterols, tocopherols, carotenoids, and phenolic compounds, have been the focal point of numerous studies.…”
Section: Introductionmentioning
confidence: 99%
“…In that sense, seed oils, especially cold-pressed seed oils, laden with polyunsaturated fatty acids (PUFA), sterols, tocopherols, carotenoids, and phenolic compounds, have been the focal point of numerous studies. The synergistic interplay of these components at varying concentrations can potentially bolster cancer therapeutics [ 10 , 11 , 12 , 13 , 14 ]. Plant oils are ideal candidates as chemopreventive agents because they are non-genotoxic and are able to effectively inhibit the formation of 17b-estradiol epoxide (E2), which is responsible for the induction of the basic mechanism of breast cancer initiation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%